How Does Mindfulness Alleviate Panic Buying: The Mediating Role of Social Alienation and Death Anxiety - Tan Y; Huang R; Chen Z (Psychology Research and Behavior Management)
Yuxuan Tan,1,2 Rong Huang,3 Zhuo Chen4 1School of Business, Central South University of Forestry and Technology, Changsha, Hunan, People’s Republic of China; 2Institute of Green Development of Hunan Province, Changsha, Hunan, People’s Republic of China; 3School of Business, Central South University, Changsha, Hunan, People’s Republic of China; 4School of Economics and Management, Jiangxi University of Finance and Economics, Nanchang, Jiangxi, People’s Republic of ChinaCorrespondence: Rong Huang, School of Business, Central South University, Changsha, Hunan, People’s Republic of China, Email 211601040@csu.edu.cnPurpose: Health crises and disease outbreaks can trigger public fear, leading to behaviors such as panic buying. It’s crucial to learn from past outbreaks and identify factors that can curb panic buying, enabling more effective management of this phenomenon. Although mindfulness has been shown to influence individual consumption behavior, no research to date has explored its association with panic buying. This research utilizes terror management theory to investigate the influence of mindfulness, as a personality trait, on panic buying during a health crisis, and to explore the sequential mediating roles of social alienation and death anxiety.Methods: A two-wave survey was administered to 342 Chinese college students during the COVID-19 outbreak. Initially, students provided their mindfulness levels and demographic information. A week later, participants who had completed the first wave reported their panic buying intentions, social alienation, and death anxiety.Results: Structural Equation Modeling analysis revealed a negative relationship between mindfulness and panic buying, with social alienation and death anxiety acting as both parallel and serial mediators in this relationship.Conclusion: Our research deepens the understanding of mindfulness from a consumer behavior perspective, fills a gap in the study of mindfulness and panic buying, and uncovers the “black box” of this relationship. The findings highlight the potential of mindfulness in mitigating panic buying during crises, offering practical implications for managing pandemic-related challenges and providing valuable insights for future research on mindful consumption.Keywords: mindfulness, panic buying, social alienation, death anxiety